2021
DOI: 10.3390/fermentation7040243
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol Production by Candida Species from Hydrolysates of Agricultural Residues and Grasses

Abstract: Xylitol is an industrially important chemical due to its commercial applications. The use of xylitol as a sweetener as well as its utilization in biomedical applications has made it a high value specialty chemical. Although several species of yeast synthesize xylitol, this review focusses on the species of the genus Candida. The importance of the enzyme xylitol reductase present in Candida species as it relates to their ability to synthesize xylitol was examined. Another focus of this work was to review prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In a recent review on Candida spp. yeast for xylitol production from agricultural residues and grasses, only one out of 25 studies reported a titre greater than 100 g L −1 , productivity of 2.8 g L −1 h −1 and yield of 0.86 g/g of xylose in 39 h from sugarcane bagasse hydrolysate (West 2021). As discussed in the Fazer competitive scenario, these data suggest that fermentative processes for xylitol production need to be significantly intensified.…”
Section: Identifying Technology Gaps Process Changes and Challenges I...mentioning
confidence: 96%
“…In a recent review on Candida spp. yeast for xylitol production from agricultural residues and grasses, only one out of 25 studies reported a titre greater than 100 g L −1 , productivity of 2.8 g L −1 h −1 and yield of 0.86 g/g of xylose in 39 h from sugarcane bagasse hydrolysate (West 2021). As discussed in the Fazer competitive scenario, these data suggest that fermentative processes for xylitol production need to be significantly intensified.…”
Section: Identifying Technology Gaps Process Changes and Challenges I...mentioning
confidence: 96%
“…Previous studies examined xylitol production using different types of microorganism and agricultural wastes by fermentation. West [37] reviewed xylitol production by Candida species from hydrolysates of agricultural residues, such as apple pomace, banana leaves, chestnut shells, cocoa pod husks, corncob, cotton stalk, olive pomace, olive pruning, rapeseed straw, rice straw, sisal fiber sugarcane bagasse, sugarcane straw, water hyacinth leaves, wheat bran, and grasses. The xylitol concentrations were in the range of 3.5-109.5 g/L.…”
Section: Xylitol Productionmentioning
confidence: 99%
“…Characterization of xylose reductase from a Candida tropicalis strain showed that the enzyme was active at a pH of 5 to 7 (Rafiqul et al, 2015b). The optimum pH for the production of xylitol by Candida strains has been reported to be 5 and 5.5 (Rudrangi and West, 2020;West, 2021). The production of xylitol by yeast generally employs a temperature of 30 • C. However, depending on the species used, the optimum temperature range of xylitol producing yeast varies between 30 and 37 • C. In a study employing Candida tropicalis for the production of xylitol, it was observed that there was a consumption of about 90% xylose at a temperature range of 29 and 34 • C and there was a decrease in xylose consumption below 28 • C and above 35 • C (Tamburini et al, 2015).…”
Section: Fermentation Strategies In Xylitol Production Fermentative P...mentioning
confidence: 99%